2004
DOI: 10.1023/b:ddas.0000026305.20852.41
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Electroacupuncture and Moxibustion in the Gastrointestinal Motility of the Rat

Abstract: We compared the outcomes of the stimulation of specific sets of acupoints with either acupuncture or moxibustion over peristalsis. Twenty-five plastic beads were orally administered in the stomach of the rats and 90 min later animals were sacrificed, the stomach and small intestine were opened, and the number of beads remaining in each segment was counted. Forty rats were immobilized for 20 min and stimulated at either abdominal or hindlimbs acupoints, with either electroacupuncture or moxibustion. Under this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 9 publications
3
31
1
Order By: Relevance
“…Although acupuncture has been reported to accelerate gastric emptying in animals and patients (6,7,10,25,26), the data of the present study are not fully consistent with this. Gastroparesis symptoms may be incited by various etiologies, including functional dyspepsia and chronic gastritis.…”
Section: Discussioncontrasting
confidence: 99%
“…Although acupuncture has been reported to accelerate gastric emptying in animals and patients (6,7,10,25,26), the data of the present study are not fully consistent with this. Gastroparesis symptoms may be incited by various etiologies, including functional dyspepsia and chronic gastritis.…”
Section: Discussioncontrasting
confidence: 99%
“…Oriental medicine routinely uses acupoint stimulation to treat internal organ-related diseases [4,12]. It has been reported that acupuncture of Heart Meridian points improved myocardial function [7,18,19,24], and acupuncture of Stomach Meridian points, like ST36, increased or decreased gastric motility in human and animal models, depending on whether or not the stomach was hypoactive or hyperactive, respectively [5,15,25].…”
mentioning
confidence: 99%
“…However, some studies have examined and reported positive acupuncture effects on gastric movement and acid secretion in animal models (32).…”
Section: Discussionmentioning
confidence: 99%